The influence of helminthiasis on the cognitive performance of school children: A meta-analysis - Soberano, Katherina J. (Animo Repository, 2021)
A meta-analysis was performed to assess the physiologic effects of helminth infection and investigate its influence on academic performance to identify control initiatives that could improve the health of school children. This study was conducted using Review Manager 5.4 to examine the impact of infection on nutritional and anemic status and cognitive performance to develop an emphasis on a multi-faceted control strategy for implementation in the Philippines. Researchers evaluated 67 journal articles from electronic databases. The included studies were subjected to a publication bias assessment and meta-analysis using a data management software. Outcomes were presented in a forest plot to summarize the findings. Results from the meta-analyses performed for physiological effects showed that none of the three parasites (Ascaris lumbricoides, Trichuris Trichiura, and hookworms) were significantly associated with the risk of malnutrition and that only hookworms were found to be significantly associated with the risk of anemia. The meta-analyses performed for cognitive function found that only the domains of memory under infected and uninfected groups and reaction time under treatment and placebo groups showed significant association between infection and poor cognitive performance. The results suggest that the detrimental effects of parasitic infection require a greater understanding of its physiologic and cognitive features due to its complexity. Anthelmintic treatment is not sufficient to alleviate the burdens of disease and must be supplemented with initiatives that allow social mobility, health education and sanitation development. Keywords: Trichuris, Ascaris, hookworm, malnutrition, anemia, memory, learning, reaction time, cognition, school children, academic performance